Cyclic single-molecule magnets: from the odd-numbered heptanuclear to a dimer of heptanuclear dysprosium clusters. Issue 11 (5th January 2016) - Tian, Haiquan; Bao, Song-Song; Zheng, Li-Min
Abstract : A heptanuclear compound and a dimer of heptanuclear dysprosium clusters (Dy7 and Dy14 ) have been successfully synthesized, which feature the largest odd-numbered cyclic lanthanide clusters reported thus far. Both exhibit single molecule magnet behaviours at low temperature. Abstract : A heptanuclear and a dimer of heptanuclear dysprosium clusters (Dy7 and Dy14 ) have been successfully synthesized by ingenious coalescence of the single and double pyrazinyl hydrazone as well as phosphonate ligands. The complexes feature the largest odd-numbered cyclic lanthanide clusters reported thus far. Both exhibit single molecule magnet behaviors at low temperature.